A study on the determinants of private car ownership in China: Findings from the panel data. (March 2016) - Wu, Na; Zhao, Shengchuan; Zhang, Qi
Highlights: We examine the determinants of private car ownership in China using panel data. The fixed effect model performs better than the pooled regression model and the random effect model. There are variations of private car ownership among cities and regions. Different policies should be adopted by cities based on their characteristics. Abstract: This study examines the determinants of private car ownership in China. The target cities are 32 provincial capital cities and the target period is from 2001 to 2011. In order to capture the individual effects (heterogeneity), the fixed and random effect models are adopted and compared, in which 8 explanatory variables are selected to include economic characteristics, urban characteristics, and transportation characteristics. Moreover, double natural logarithm model is employed to measure the elastic relationship between the private car ownership and regressors. The estimated results show that the fixed effect model performs better than pooled regression model and the random effect model. In addition, there are variations of private car ownership among cities and regions. Finally, the influence of factors responsible for these variations is also presented and discussed in this paper.